Community Satisfaction with Zamboanga City Jail Services: Toward a Trust Rating Index - Aznar, Erizha Mae; Noceda, Ezrha Joy F; Villa, Jay Rim; Polingga-Villa, Laiza Jane L (Future Science / FSH-PH Publications, 2025)
This study assesses the levels of trust, respect, and satisfaction among clients of the Bureau of Jail Management and Penology (BJMP) in Zamboanga City Jail. As a vital institution within the Philippine correctional system, the BJMP plays a key role in upholding humane safekeeping and rehabilitation. Understanding client perceptions within this facility provides valuable insights into the effectiveness and quality of jail management and service delivery. Rooted in the constitutional principle that “public office is a public trust,” the research addresses a critical gap in empirical data on public perception of jail institutions. Using a descriptive research design, the study surveyed 300 respondents—persons deprived of liberty (PDL), their family members, and service providers—selected through purposive sampling. A validated questionnaire measured perceptions of trust, respect, and service satisfaction. Findings revealed a consistently high level of trust (overall trust index of 97%) and satisfaction across all groups, with mean scores above 5.70 on a six-point scale, indicating a